Lesson Learned of Rohingya Persecution in Myanmar for Sustainable Development and Policy Transformation in Malaysia - Aizat Khairi; Suyatno Ladiqi; Sarah Nadiah Rashidi (Journal of Public Administration and Government, 2020)
This paper examines about the lesson learned of persecuted Rohingya people in Myanmar. The Myanmar regime does not recognize the Rohingyas as their people and accused them as Bengalis from Bangladesh. The issue of denied citizenship has caused the Rohingya people to live in limbo. Unlike other ethnics in Myanmar, they are denied the rights as sovereign citizens. The situation becomes worse when the other local citizens, for the reason of ethnic and religion matters, join forces with the regime in violating and abusing the Rohingyas. Therefore, the Rohingyas are left as stateless people in their own country and are forced to become refugees to seek a better life. The case of the Rohingya people in Myanmar can be a lesson learned for Malaysians who are living in a multi-society country. The government and the people have to be aware that unfair policy and physical violence could increase the intensity of conflict and cause bad implication in terms of peace and harmony in the country. Hence, several possible peace process initiatives of sustainable development must be introduced to transform the certain policy and further strengthen the ethnic relation in Malaysia to ensure everyone lives together in peace and harmony.